2022
DOI: 10.3390/ijms23168904
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Preclinical Research: A Systematic Review on Comparative Studies Using Ovariectomized Sheep

Abstract: Sheep ovariectomy (OVX) alone or associated to steroid therapy, deficient diet, or hypothalamic–pituitary disconnection has proven to be of critical importance for osteoporosis research in orthopedics. However, the impact of specific variables, such as breed, age, diet, time after OVX, and other variables, should be monitored. Thus, the design of comparative studies is mandatory to minimize the impact of these variables or to recognize the presence of unwanted variables as well as to better characterize bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A large body of literature in both animal models and humans has demonstrated that estrogen deficiency leads to accelerated bone loss, increased bone resorbing osteoclastic activity, and impaired bone formation [40]. Similar effects were observed in OVX mice [41] and sheep [42]. Also, in human observational studies, postmenopausal period results in accelerated bone loss in both trabecular and cortical bone, leading to an increased risk of fracture [43].…”
Section: Postmenopausal Skeleton and Hrtmentioning
confidence: 82%
“…A large body of literature in both animal models and humans has demonstrated that estrogen deficiency leads to accelerated bone loss, increased bone resorbing osteoclastic activity, and impaired bone formation [40]. Similar effects were observed in OVX mice [41] and sheep [42]. Also, in human observational studies, postmenopausal period results in accelerated bone loss in both trabecular and cortical bone, leading to an increased risk of fracture [43].…”
Section: Postmenopausal Skeleton and Hrtmentioning
confidence: 82%
“…Although several mouse and rat models of bone loss have been developed, the mouse model of post-menopausal osteoporosis from ovariectomy is the most used [9]. Post-menopausal osteoporosis from ovariectomy was also studied in a sheep model [10]. Other mouse or rat models of bone loss are based on skeleton disuse, lactation-induced bone loss, glucocorticoid excess, bone loss associated with erythropoietin receptor signaling, or models of bone loss associated with a hypoxia environment [9,11].…”
mentioning
confidence: 99%